Pro-Coagulant Endothelial Dysfunction Results from EHEC Shiga Toxins and Host Damage-Associated Molecular Patterns - Mayer, Chad L.; Parello, Caitlin S. L.; Lee, Benjamin C.; Itagaki, Kiyoshi; Kurosawa, Shinichiro; Stearns-Kurosawa, Deborah J. (Frontiers in Immunology, 2015)
Hemolytic uremic syndrome (HUS) from enterohemorrhagic E.coli infection (EHEC) is a leading cause of kidney failure in otherwise healthy U.S. children. The bacterial Shiga toxins (Stx) induce the characteristic coagulopathy of HUS, but the cell and organ damage during infection likely also releases inflammatory damage-associated molecular patterns (DAMPs) that may exacerbate injury in concert with the toxins. To examine this, aortic and renal glomerular cell anticoagulant and barrier functions were studied after in vitro challenge with Stx1, Stx2 and DAMPs. There was significant loss of surface anticoagulant protein C pathway molecules, increased expression of prothrombotic PAR1 and reduced protein C activation capability by 15-27%. Histones nearly completely prevented activated protein C protection of endothelial cells from thrombin-induced permeability. In mice, lethal Stx2 challenge elevated plasma HMGB1 (day 2, 321±118%; p<0.01) and extracellular histones (day 3, 158±62%; p<0.01). Mice colonized with Stx2-expressing Citrobacter rodentium developed increased HMGB1 (day 5, 155±55%; p<0.01) and histones (day 3, 378±188%; p<0.01). Anti-histone antibody reduced both DAMPs to baseline, but was not sufficient to improve survival outcome or kidney function. Together, these data suggest a potential role for both Stx and DAMPs in producing endothelial injury and a prothrombotic environment.